Effect od ascorbic on intragastric bacterial ocergrowth and nitrite formation - Levent DEMİRTÜRK,; Saadeddin HÜLAGÜ,; Melih ÖZEL,; Mehmet ALTIN,; Ömer KOCABEYOĞLU,; A. Kemal GÜRBÜZ,; İlhan BİRİNCİ,; Özkan ÖZBAŞ,; Ali ÖZCAN,; Hüseyin BALOĞLU, (Turkish Journal of Gastroenterology, 2019)
-